Obsequium amicos, veritas odium parit: Petrarca és Cicero "barátsága" - Lázár, István Dávid (Antikvitás & Reneszánsz, 2018)
It is an often mentioned and well-known fact, that Cicero was the closest to Petrarch among the greatest of the ancient world. This is evidenced, among other things, by the fact that he quotes him for countless times, often very long, and that in the Rerum familiarium libri XXIV, which was inspired by Cicero, in the letter group called by the summarizing title Antiquis illustrioribus collection, two epistles are addressed only to him. Almost without exception, Petrarch selects in his moral philosophical writings one work of Cicero as a starting point, and elaborates his own thoughts reflecting on the antique predecessor’s views. In my presentation, I outline some of these, and with its help I try to present the “friendship” that spans thousands of years.